Efeito do auto-conceito de alunos do ensino médio e das relações familiares no bullying entre pares - Arslan Sevda; Savaser Sevim (Universidade de Fortaleza, 2012)
Objective: To determine the role of high school students in the cycle of bullying, their selfconcept and the effect of family characteristics associated with the bullying. Methods: We conducted a descriptive, comparative and correlational study. The survey data were collected in the largest province of Turkey, Istanbul, with 1670 students in ninth and tenth grades in six (2 regular, 2 occupational and 2 private) high schools, chosen to represent the types of schools affiliated to Ministry of Education. Data were collected through four different data collection tools: Multidimensional Scale of Peer Victimization, Self-Concept Scale Piers-Harris Children's, Family Assessment Device and a personal information form. Results: According to the Victimization Scale, 17% of students were in the cycle of bullying (5.3% of aggressors, victims of 5.9%, 5.8% both aggressors as victims). The bullying was significantly more common in the mother-father separated group, in the group that had witnessed violence between family members and those who had been treated violently by family members. Bullying was significantly lower in students with healthy families compared with those who do not have healthy families and students with high average score on the selfconcept compared to those with low average score. Conclusions: This study shows the need to implement effective measures to prevent bullying in schools. Based on the results of the study, it should be emphasized that education can be directed to families through programs to prevent bullying. The focus of the implementation can be concentrated on the effect of family relations on students' behavior. The existing programs of bullying prevention can be directed to increase the level of self-esteem of students with low self-esteem, because they are more likely to become involved in bullying incidents